Relationship of water consumption, speed suitability, and fatigue to accidents in online motorcycle taxi drivers - Widajati, Noeroel; Dzaki, Muhammad; Dwiyanti, Endang; Mohd Elias, Saliza; Jalaludin, Juliana; Irmawati, Anis; Priyandani, Yuni (Universiti Putra Malaysia Press, 2024)
Introduction: Working as an online motorcycle taxi that spends extended periods in a hot environment increases the risk of dehydration and accidents if not mitigated by adequate fluid consumption. Additionally, excessive vehicle speed and fatigued driving increase the likelihood of being involved in an accident. This study aims to determine the significant relationship between water consumption, speed suitability, fatigue and the occurrence of accidents among online motorcycle taxi drivers. Methods: The study employed an observational cross-sectional approach with 110 online motorcycle taxi drivers in Sidoarjo. Data on water consumption, speed suitability, accidents were collected via a Google form, while fatigue was assessed with the Subjective Rating Test Questionnaire. Statistical analysis used Cramer’s V to link water consumption with accidents and the contingency coefficient test to examine speed suitability, fatigue, and accidents. Results: The results of the analysis indicate a positive relationship with a weak relationship between water consumption (r = 0.227) and speed suitability (CI = 0.220) and the occurrence of accidents, as well as a strong relationship and positive relationship between fatigue (CI = 0.289) and the occurrence of accidents among online motorcycle taxi drivers. Conclusion: There is a relationship between water consumption, speed suitability, fatigue, and accidents among online motorcycle taxi drivers. Fatigue notably strongly correlates with accidents. Drivers are urged to avoid exceeding 8-hour workdays or driving while fatigued (e.g., drowsy, uncomfortable, in pain).